Fish fauna composition and water quality at Batang Ai hydroelectric reservoir, Lubok Antu, Sarawak - Nur Ezzaty, Nazarudin (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study was carried out in October 2014 and February 2015 to determine the fish species composition and water quality at Batang Ai Hydroelectric reservoir area. A total of six sampling stations were selected in this tudy. Fourteen water quality parameters were documented based on in-situ and ex-situ laboratory analysis that were carried out according to the APHA (2000) methods. A total of 992 individuals consisting of 20 species from 8 families were caught in Batang Ai Hydro-electric reservoir. The three most dominant species were Cyclocheilichti1ys apogon, Osteochilus wandersii and Barbonymus schwanenfeldii. Results for in-situ water qual ity parameters were pH (6.22-8.32), dissolved oxygen (0.7-8.3 mglL), conductivity (6.3-120.7 !-IS/cm), temperature (26.3-31 .3 °C), transparency (1 .02-4.27 m) and turbidity (0.00-34.66 FNU). For ex-situ water quality parameters, results of BODs ranged from 0.7-6.3 mg/L, TSS (0.002-0.043 giL), chlorophyll-a (1.70 to 35.85 mglL) and for nutrients (ammonical nitrogen: 0.03 to 2.53 mglL; nitrate: 0.01 to 0.21 mg/L; orthophosphate: 0.02 to 2.04 mg/L and Nitrite: 0.001 to 0.117 mg/L). The fisheries production of Batang Ai Hydroelectric Reservoir was estimated to be 1'1.17 kg ha -I yr- I to 20.67 kg ha-I yr-I . Aquaculture and other anthropogenic activities occurring within the surrounding areas of the reservoir may have negatively impacted the water quality of Batang Ai Hydro-electric reservoir.